Asymmetric communication: cognitive models of humans toward an android robot - Kawakubo, Daisuke; Shuzo, Masaki; Sugiyama, Hiroaki; Maeda, Eisaku (Frontiers in Robotics and AI, 2024)
In the development of dialogue systems for android robots, the goal is to achieve `human-like' communication. However, subtle differences between android robots and humans are noticeable, leading even human-like android robots to be perceived differently. Understanding how humans accept android robots and optimizing their behavior is crucial. Generally, human customers have various expectations and anxieties when interacting with a robotic salesclerk instead of a human. Asymmetric communication (AC) arises when android robots treat customers like humans while customers treat robots as machines. Focusing on human-robot interaction in a tourist guide scenario, In this paper, we propose an AC strategy that does not use estimation technology for preference information, but instead performs changing the agent's character in order to pretend to tailor to the customer. In line with this, we prepared an experimental method to evaluate AC strategies, using video clips to simulate dialogues. Participants completed questionnaires without prior knowledge of whether the salesclerk was human-like or robotic. The method allowed us to assess how participants treated the salesclerk and the effectiveness of the AC strategy. Additionally, during our demonstration in a dialogue robot competition, 29 visitors had a positive impression of the android robot's AC strategy and reported a high level of satisfaction with the dialogue.